Cerebral cortex : principles of operation - Rolls, Edmund T. (Oxford : Oxford University Press, 2016)
This work provides insights into the principles of operation of the cerebral cortex. These principles are key to understanding how we, as humans, function. The author includes appendices on the operation of many of the neuronal networks described in the book.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 26, 2016).
Keywords: Cerebral cortex